Inflammatory biomarkers on an LPS-induced RAW 264.7 cell model: a systematic review and meta-analysis - Facchin, Bruno Matheus; dos Reis, Gustavo Oliveira; Vieira, Guilherme Nicácio; Mohr, Eduarda Talita Bramorski; da Rosa, Júlia Salvan; Kretzer, Iara Fabricia; Demarchi, Izabel Galhardo; Dalmarco, Eduardo Monguilhott (Inflammation research, 2022)
Introduction Several experimental models have been designed to promote the development of new anti-inflammatory drugs. The in vitro model using RAW 264.7 cells has been widely used. However, there is still no consensus on which inflammatory mediators should initially be measured to screen for possible anti-inflammatory effects. To determine the rationality of measuring inflammatory mediators together with NO, such as the levels of tumor necrosis factor (TNF)-α, and interleukins (IL) 1β and 6, we carried out this systematic review (SR) and meta-analysis (MA). Methodology We conducted this SR and MA in accordance with the Preferred Reporting of Systematic Reviews and Meta-Analysis and the Cochrane Handbook for Systematic Reviews of Intervention. This review was registered in the Open Science Framework ( https://doi.org/10.17605/OSF.IO/8C3HT ). Results LPS-induced cells produced high NO levels compared to non-LPS induced, and this production was not related to cell density. TNF-α, IL-1β, and IL-6, also showed high levels after cells had been stimulated with LPS. Though with some restrictions, all studies were reliable, as the risk of bias was detected in the test compounds and systems. Conclusion Measurement of NO levels may be sufficient to screen for possible anti-inflammatory action in the context of LPS-induced RAW 264.7 cells.